Association of acute blood biomarkers with diffusion tensor imaging and outcome in patients with traumatic brain injury presenting with GCS of 13–15 - Mononen, Malla; Mohammadian, Mehrbod; Hossain, Iftakher; Roine, Timo; Tenovuo, Olli; Blennow, Kaj; Gill, Jessica; van Gils, Mark; Hutchinson, Peter; Luoto, Teemu M.; Maanpää, Henna-Riikka; Menon, David K.; et al. (Elsevier BV, 2026)
The aim of the study was to assess the association between blood-based biomarkers of different cellular origins and later white matter integrity, measured using post-acute diffusion tensor metrics, and their relation to outcome in patients presenting with Glasgow Coma Scale of 13–15 after traumatic brain injury (TBI).
Admission plasma samples for glial fibrillary acidic protein (GFAP), interleukin 10 (IL-10), heart fatty-acid binding protein (H-FABP), S100 calcium-binding protein B (S100B), total tau (T-tau), and amyloid beta 40 and 42 (Aβ40 and Aβ42) were taken for 92 patients. Diffusion-weighted magnetic resonance imaging (DW-MRI) and outcome evaluation was done ≥ 90 days post-injury. Outcome was assessed using Glasgow Outcome Scale-Extended (GOSE) and dichotomized as complete (GOSE 8) and incomplete (GOSE < 8) recovery. Mean fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) were calculated from the skeletonized white matter tracts of the whole brain.
​​​​​​​
IL-10 and T-tau showed significant weak-moderate negative correlations with FA, and significant positive correlations with MD and RD in incompletely recovered patients. GFAP showed significant weak positive correlations with MD and RD, while its correlation with FA was slightly below significance threshold after correction for multiple comparison in incompletely recovered patients. Similar trends were observed in the whole cohort and in the CT-positive cohort, although these did not reach statistical significance.
​​​​​​​
Higher acute levels of GFAP, IL-10 and T-tau may be associated with the development of axonal injury. If validated in future studies, these biomarkers may help identify patients who require closer follow-up and DW-MRI.